The Molecular and Cellular Basis for Parkinson's Disease - Müller, Thomas (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The focus on dopamine-sensitive motor symptoms, in association with the improvement of motor complications in the heterogeneous disease entity Parkinson's disease, has led to a certain standstill in research. This Special Issue provides new concepts and new ideas on the pathogenesis, genetics, and clinical maintenance of Parkinson's disease and related disorders. Not only new experimental findings, but also clinical outcomes, case series, and research on alternative, non-pharmacological therapies are included. The objective is to bridge the currently increasing gap between experimental and clinical research on Parkinson's disease and related disorders.
English
Keywords: microRNAs; disease-modifying effects; SH-SY5Y; inpatient treatment; sphingolipids; neurodegeneration; magnetic resonance spectroscopy; MO3.13; schizophrenia; epigenetics; long-chain acylcarnitine; molecular mimicry; curli; multimodal complex treatment; chlorogenic acid; glycerophospholipids; caffeic acid; lipoproteins; myenteric plexus; neurometabolites; HOG; immature oligodendrocyte; autophagy; oligodendrocyte; hypochlorite; alpha-synuclein; microbiome; glucocerebrosidase; Lewy Body Dementia; brain iron; mesenchymal stem cells; fatty acid ?-oxidation; GABA; enteric glial cell; gut-brain axis; microbiota; REM sleep behavior disorders; redox cycling; magnetic resonance imaging; differentiation; ?-synuclein-mediated pathology; Parkinson disease; Gaucher s disease; metallothionein; [123I]FP-CIT-SPECT; dopaminergic neuron; mature oligodendrocyte; glycerolipids; spectroscopy; neuroinflammation; exosomes; immunotherapy; DNA methylation; sterol lipids; nigral cells; cell line; cysteinyl-dopamine; myelin; parkinsonisms; multiple sclerosis